A democratic nuclear energy transition? Public participation in nuclear activities. Issue 2 (16th February 2022) - Duvic‐Paoli, Leslie‐Anne; Lueger, Priska
Abstract: Governments, local authorities and civil society organizations are becoming increasingly vocal regarding the domestic and transboundary risks that nuclear power represents to health and the environment. While participatory rights are gaining importance in the nuclear sector, nuclear‐related activities have been at the centre of inconsistencies and uncertainties in the practice of public participation under the Aarhus and Espoo Conventions. Against this background, this article analyses the interactions between international environmental law and international nuclear law to understand how environmental democracy principles apply in the context of nuclear activities. It presents the relationship as mutually beneficial: despite inherent tensions due to the nature of nuclear activities, these interactions hold important promises to democratize the nuclear field on the one hand and strengthen environmental democracy on the other.